Early-stage life cycle assessment for sustainable design of wearable microfluidic sweat sensor: continuous dehydration monitoring - Rabost-Garcia, Genis; Sanchez, David; Nacher-Castellet, Victor; Fajardo, Andrea; Ymbern, Oriol; Muñoz-Pascual, Xavier; Alvarez, Albert; Punter-Villagrasa, Jaime; Casals-Terré, Jasmina; Heredia, Ricardo; Espinoza, Fernando; Moreno-Simonet, Lia; et al. (Frontiers in Lab on a Chip Technologies, 2025)
IntroductionWearable sweat sensors are emerging as non-invasive tools for health monitoring and point-of-care diagnostics. However, their single-use nature and complex manufacturing processes pose significant sustainability challenges. This research integrates Life Cycle Assessment (LCA) at the design stage to address these environmental concerns, using it as a decision-making tool to guide material selection.MethodsWe developed an integrated capacitive sensor for continuous sweat rate and dehydration monitoring. The study’s focus was on replacing conventional silver-printed electrodes with more sustainable alternatives. We specifically investigated the viability of using copper-based laminates and screen-printed graphite as alternative electrode materials, assessing their performance against the original silver electrodes. A comprehensive LCA was performed to evaluate the environmental footprint of the device’s manufacturing and assembly processes.ResultsOur findings demonstrate that both copper-based laminates and screen-printed graphite are viable substitutes for silver-printed electrodes, maintaining functional performance while significantly reducing the device’s environmental impact. The LCA data confirmed that these material substitutions lowered the overall environmental footprint of the wearable sweat sensors.DiscussionThis work underscores the critical role of integrating sustainability principles and tools like LCA early in the design phase of medical devices. By making informed material choices, it is possible to develop functional, high-performance wearable sensors that are also environmentally conscious. This approach offers a practical pathway toward scalable, sustainable, and net-zero healthcare technologies.